PERAN PARTISIPASI MASYARAKAT DESA DALAM PROSES KEBIJAKAN PUBLIK DI DESA PERKEBUNAN GELUGUR KECAMATAN SALAPIAN KABUPATEN LANGKAT (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the form of village community participation in the public policy process, the challenges faced by the village government in encouraging community participation in the public policy process, and the influence of village community participation in the public policy process in Gelugur Plantation Village, Salapian District, Langkat Regency. Where Gelugur Plantation Village, Salapian District, Langkat Regency, is one of the villages that handles issues regarding the Village Decision. As a village with a fairly dense population and diverse community backgrounds. Where the selected community has diverse characteristics, such as farmers, traders and other workers. The research method used is qualitative descriptive research with data collection through observation, interviews, documentation. The research location was carried out in Gelugur Plantation Village, Salapian District, Langkat Regency. In this study, the informants used were the village head and 15 community members. Using data analysis techniques, namely data reduction, data presentation, and data verification. In this research, high community participation makes village policies more targeted, easier to implement, and gain broad support from residents, where community participation has a very important role in determining the quality and success of public policies in the village. Community participation is seen through their active involvement in deliberations at the hamlet level to village deliberations, providing proposals for development programs, and implementing activities through mutual cooperation and cooperation in physical development and community empowerment. However, the village government still faces several obstacles in encouraging more optimal participation, such as the low understanding of some residents regarding policy mechanisms, the level of community busyness in daily work, and limited information received by the community regarding village assistance rules and procedures.